EUPHORIA OF INDEPENDENT LEARNING CAMPUS INDEPENDENT (MBKM) MULTICULTURAL PERSPECTIVE; OPPORTUNITIES AND CHALLENGES OF EDUCATION SYSTEM FOR GEN Z - BZ, Zakiyah; Febri, Riski; Utari, Dita; Hasanah, Uswatun; Aini, Riza Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of the Merdeka Belajar Kampus Merdeka policy is to encourage students to master various fields of science with their areas of expertise, so that they are ready to compete in the global world. This policy gives students the opportunity to choose the courses they will take based on their own wishes. The implementation of the Independent Campus Learning policy encourages the learning process in higher education to become more autonomous and flexible. Education always strives to create students who always make updates all the time. Not only highly educated but able to be an agent of change in small and large scopes. The resulting changes and innovations are able to provide maximum contribution to the progress of a nation so that it has quality human resources. In writing this article, we used qualitative research methods and approaches with the type of library study. The learning process on an independent campus is one manifestation of student-centered learning which is very essential. Learning on an independent campus provides opportunities as well as challenges and opportunities for developing innovation, creativity, capacity, personality and student needs, as well as developing independence in seeking and finding knowledge through the realities and dynamics of the field such as ability requirements, real problems, social interaction, collaboration, management self, performance demands, targets and achievements. Through the Merdeka Belajar program which is well designed and implemented, students' hard skills and soft skills will be formed strongly. However, a curriculum that is considered to be able to develop student capacity has challenges that must be faced and prepared for by the implementing agency Merdeka Belajar Kampus Merdeka (MBKM). Among the opportunities for implementing BMKM are collaborative learning-based learning, encouraging opportunities for cooperation and fostering a sense of diversity in accordance with the mandate of Pancasila as the basic norm of the Unitary State of the Republic of Indonesia (NKRI). The challenges are technical, namely the established program implementation mechanisms, accessibility of information and communication technology and human resources (HR). Talking about the accessibility of information technology is closely related to the thinking patterns of generation Z.